Synthesis and biological evaluation of N9-cis-cyclobutylpurine derivatives for use as cyclin-dependent kinase (CDK) inhibitors. Issue 18 (15th September 2017) - Park, Sun Jun; Kim, Eunjin; Yoo, Miyoun; Lee, Joo-Youn; Park, Chi Hoon; Hwang, Jong Yeon; Ha, Jae Du
Graphical abstract: Abstract: A novel 6-aminopurine scaffold bearing an N 9- cis -cyclobutyl moiety was designed using structure-based molecular design based on two known CDK inhibitors, dinaciclib and Cmpd-27. A series of novel 6-aminopurine compounds was prepared for structure–activity relationship (SAR) studies of CDK2 and CDK5 inhibitors. Among the compounds synthesized, compound8l displayed potent CDK2 and CDK5 inhibitory activities with low nanomolar ranges (IC50  = 2.1 and 4.8 nM, respectively) and showed moderate cytotoxicity in HCT116 colon cancer and MCF7 breast cancer cell lines. Here, we report the synthesis and evaluation of novel 6-aminopurine derivatives and present molecular docking models of compound81 with CDK2 and CDK5.